FORMULATION AND EVALUATION OF METRONIDAZOLE MICROSPHERES-LOADED BIOADHESIVE VAGINAL GEL - Kalita, Banasmita; Saikia, Kritika; Kalita, Bhupen (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objectives: The objective of the present work is to develop and characterize metronidazole microsphere-loaded bioadhesive vaginal gel to ensure longer residence time at the infection site, providing a favorable release profile for the drug. Methods: Microsphere was prepared by solvent evaporation method in various ratios of metronidazole to poly-Îµ-caprolactone (PCL). Physicochemical evaluation of microspheres includes determination of solubility in simulated vaginal fluid, partition coefficient (n-octanol/citrate phosphate buffer pH 4.5), particle size distribution, entrapment efficiency, X-ray diffraction, and surface morphology by scanning electron microscopy (SEM). Drug excipient compatibility was established by Fourier transform infrared and differential scanning calorimetry studies. Bioadhesive gel was prepared using Carbopol 934P and HPMC K4M in various concentrations, and methyl paraben was used as a preservative. The pH was adjusted with triethanolamine which resulted in a translucent gel. The optimized metronidazole microsphere formulation was dispersed into the gel base. Microspheres in gel formulations were evaluated for pH, viscosity, spreadability, drug content, and gelling strength. Ex vivo mucoadhesive strength of the gel was determined on goat vaginal mucosa. In vitro drug release study was performed using cellophane membrane. Results: The optimized batch of microsphere F4 (drug-polymer ratio 1:4) showed entrapment efficiency of 72.62Â±3.66%, solubility of 1.5 mg/ml, and partition coefficient of 0.12. Particle size of all the formulations was observed below 100 Î¼m. Regular and spherical particles were observed in the SEM photomicrographs. The optimized gel formulation G5 (Carbopol and HPMC at 1: 0.25 ratio) showed viscosity of 7538 cps at 100 RPM, gel strength recorded as 35 secobds for a 1000.00 mg load, and spreadability of 4.6 g.cm/seconds. G5 showed 82.4% drug release at 10.0 hrs and mucoadhesive strength of 6.5Â±1.2 g. Conclusion: The study results suggest that metronidazole-loaded PCL microsphere in mucoadhesive gel would provide a mean for sustained treatment of vaginal infections. Keywords: Microsphere, Metronidazole, Bioadhesive vaginal gel.